Neurosurgical applications of tractography in the UK. (4th July 2021) - Toescu, Sebastian M.; Hales, Patrick W.; Tisdall, Martin M.; Aquilina, Kristian; Clark, Christopher A.
Abstract: Introduction: Tractography derived from diffusion MRI can provide important insights into human brain microstructure in vivo . Neurosurgeons were quick to adopt the technique at the turn of the century, but it remains plagued by technical fallibilities. This study aims to describe how tractography is deployed clinically in a modern-day, public healthcare system, serving as a snapshot from the 'shop floor' of British neurosurgical practice. Methods: An 11-question survey was circulated to the mailing lists of the Society of British Neurological Surgeons and British Neurosurgical Trainees' Association, including questions on frequency, indication, tracts reconstructed, specific details of techniques used and personnel by whom it was performed, and a free-text section on the limitations of tractography. Results: 58 survey responses were received, covering all 40 neurosurgical units in the UK and Ireland. Overall, responses were received from neurosurgeons at 36 units (90.0%) stating tractography was in use at that unit. 74.1% of the responses were from Consultants. The most common indication for tractography was in tumour resection. It was most commonly performed by neuroradiologists or imaging scientists. 75.9% of respondents stated that the model used to process tractography was the diffusion tensor (DTI). Many respondents were unaware of which algorithm (74.1%) or software tools (65.6%) were used by the operator to produce tractography visualisations. The corticospinal tract was the most commonly reconstructed tract. The most commonly cited limitations of the technique were perceived inaccuracy and brain shift. Conclusions: In this UK-based survey of practising neurosurgeons, we show that 90% of neurosurgical units in the UK and Ireland use tractography regularly; that predominantly DTI-based reconstructions are used; that tumour resection remains the most frequent use of the technique; and that large tracts such as the corticospinal tract are most frequently identified. Many neurosurgeons remain unfamiliar with the underlying methods used to produce tractography visualisations.